Immuno-Imaging (PET/SPECT)–Quo Vadis? - Carsten S. Kramer; Antonia Dimitrakopoulou-Strauss (Molecules, 2022)
The use of immunotherapy has revolutionized the treatment regimen of certain cancer types, but response assessment has become a difficult task with conventional methods such as CT/MRT or FDG PET-CT and the classical response criteria such as RECIST or PERCIST which have been developed for chemotherapeutic treatment. Plenty of new tracers have been published to improve the assessment of treatment response and to stratify the patient population. We gathered the information on published tracers (in total, 106 individual SPECT/PET tracers were identified) and performed a descriptor-based analysis; in this way, we classify the tracers with regard to target choice, developability (probability to progress from preclinical stage into the clinic), translatability (probability to be widely applied in the ‘real world’), and (assumed) diagnostic quality. In our analysis, we show that most tracers are targeting PD-L1, PD-1, CTLA-4, and CD8 receptors by using antibodies or their fragments. Another finding is that plenty of tracers possess only minor iterations regarding chelators and nuclides instead of approaching the problem in a new innovative way. Based on the data, we suggest an orthogonal approach by targeting intracellular targets with PET-activatable small molecules that are currently underrepresented.